2021
DOI: 10.3390/ejihpe11020030
|View full text |Cite
|
Sign up to set email alerts
|

How Can Students Feel More Vital Amidst Severe Restrictions? Psychological Needs Satisfaction, Motivational Regulation and Vitality of Students during the Coronavirus Pandemic Restrictions

Abstract: During the pandemic restrictions imposed in spring 2020, many aspects of students’ living and learning environments changed drastically. From the perspective of Self-Determination Theory, changes in social context interact with the satisfaction or frustration of basic psychological needs and, as a result, with study-related motivational regulation and vitality. In this study, we investigate the relationships between the contextual factors of online-based distance learning, basic psychological needs, forms of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 67 publications
1
18
0
2
Order By: Relevance
“…We also investigated whether vitality during the forced distance learning period can be explained by BPNS and BPNF as well as the extent to which the regulatory motivational types are appropriate mediators in this relationship (hypotheses 5 and 6; see also Núñez and León, 2016 or Martinek et al, 2021 ). In line with our expectations, the results show that the satisfaction of autonomy and competence are strong predictors of self-determined types of motivation (cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also investigated whether vitality during the forced distance learning period can be explained by BPNS and BPNF as well as the extent to which the regulatory motivational types are appropriate mediators in this relationship (hypotheses 5 and 6; see also Núñez and León, 2016 or Martinek et al, 2021 ). In line with our expectations, the results show that the satisfaction of autonomy and competence are strong predictors of self-determined types of motivation (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Online situations with no direct social interactions may well be experienced as highly self-determined (e.g., Ryan et al, 2006 , 2010 ). If the other two basic psychological needs for autonomy and competence are reasonably satisfied, students may still be “well aligned with their inner selves” ( Martinek, et al, 2021 ) and the need for relatedness may play a subordinate role. Another reason could be that the basic need for relatedness is not predominantly satisfied in the study context, but by family and/or friends ( Legault et al, 2006 ; Tezci et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this pandemic has had catastrophic effects on the physical health of millions of individuals, the psychological impact of the virus has also proven detrimental [ 3 , 4 , 5 , 6 ]. The full psychological impact of the COVID-19 pandemic continues to be investigated; however, research has shown that postsecondary students are a population that is highly susceptible to psychological distress [ 3 , 7 , 8 , 9 ]. Young adults between 18 and 24 years of age, the most common age group for postsecondary students, reported the highest levels of pandemic-related psychological distress when compared to other age groups, with a quarter of them reporting suicidal thoughts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%